Case report: Pulmonary Ewing sarcoma disguised as non-small cell lung cancer - Carter, Mary E.; Benegiamo-Chilla, Alessia; Kloker, Linus D.; Paulsen, Nikolas; Potkrajcic, Vlatko; Paulsen, Frank; Nemeth, Attila; Steger, Volker; Schulze, Martin; Biskup, Saskia; Benzler, Katrin; Singer, Stephan; et al. (Frontiers in Oncology, 2024)
Ewing sarcoma is the second most common primary malignant bone cancer in children and adolescents. This rare type of cancer is characterized by its high malignancy and therefore high risk of metastases. Typically, Ewing sarcomas originate from bones. However, extraosseous Ewing sarcoma such as pulmonary Ewing sarcoma can also be found. In this case report, we present a 55-year old male patient who was initially diagnosed with non-small cell lung cancer at his local district hospital. However, the diagnosis was changed to one of pulmonary Ewing sarcoma after subsequent histopathological and molecular pathological analysis performed in a reference pathology laboratory. After patient referral to a certified (according to the German Cancer Society) high-volume sarcoma center, multimodal chemotherapy was initiated based on recently published clinical data as opposed to the more commonly used treatment regimen in Europe. The patient responded well to treatment and underwent a complete surgical tumor resection followed by radiotherapy. In summary, this case report highlights the importance of a rigorous and timely histopathological examination of biopsy samples by a specialized cancer center to enable a correct diagnosis of the cancer type. Additionally, molecular pathology plays a crucial part in this analysis and allows the necessary differentiation between cancer types. Up to now, there is no international treatment guideline available for the treatment of Ewing sarcoma. Patients should be referred to specialist centers to allow the best possible treatment of the cancer type in view of current published clinical data. In the case of Ewing sarcoma, and in accordance with the most recent research, patients should be treated with vincristine, doxorubicin and cyclophosphamide plus ifosfamide and etoposide in combination with local treatment such as surgery and/or radiotherapy because this has been demonstrated to be the more effective therapy.